Alat Ukur Alat Ukur Suhu Otomatis Menggunakan Sensor Suhu Non Contact IR (Infrared) Berbasis Arduino Nano : Pengukuran Suhu Tubuh Manusia - Sunardi; Puji Nur Setiawan (CV. Multi Kreasi Media, 2022)
Abstract− During the Covid-19 pandemic, measuring human body temperature became an important thing as an action to detect early symptoms of Covid-19, in addition as an effort to reduce direct contact and implement social distancing protocols, a study was conducted on temperature measurement which, if an abnormal measuring device will automatically issue the text displayed on the LCD screen and as an early warning. Therefore, this study aims to make an Arduino-based automatic body temperature measuring device that functions like a firing thermometer and the output will be displayed on the LCD screen. In this study, a tool has been designed that can be used to determine the value of human body temperature in a short time and produce an accurate reading value. Using an infrared sensor with the MLX90614 series combined with Arduino Nano and a 16x2 i2c LCD display is the method used to make a body thermometer without physical contact. The research method used is to analyze the results of temperature check data using this tool in several rooms such as air-conditioned rooms, indoors and in open spaces. Keywords: Arduino Nano, MLX90614, infrared, temperature sensor